Structure of Banach algebras of bounded continuous functions in the open disk which contain H∞, Hoffman algebra, and nontangential limits - Ivanov, O.V. (Український математичний журнал, 1993)
The goal of this paper is to describe the maximal ideal space M(HGB) of the algebra HGB.